POLITICAL COMMUNICATIONS IN THE SOCIAL MEDIA OF INDUSTRIAL REVOLUTION 4.0 - Zulman Barniat (DEMOKRASI, 2021)
The development of communication technology has penetrated the lives of humanity. One form of development of communication technology is the new media in industry 4.0 revolution, which then gave birth to a more sophisticated social media. The political world also on the industrial revolution 4.0 can not be separated from the influence of the development of new media and social media. Social media is like two sides of a coin to political actors. On the one hand, success in utilizing social media can enable positive support from the community. But on the other hand social media risks damaging the image that he has. The author will discuss the challenges and opportunities of social media in the 4.0 industry revolution towards political actors. Presentation of the use of social media in industry 4.0 revolution in political communication. Furthermore, the author discusses the challenges faced by political actors in industrial revolution 4.0. Furthermore, it offers an opportunity for political actors in the use of social media in industry 4.0 revolution. There is a final section that concludes what should be done by political actors to minimize risk and maximize opportunities in politics in social media industry revolution 4.0.